Women's health and the world's cities - Meleis, Afaf (City in the twenty-first century book series., 2011)
This collection of essays, written by urban planners, scholars, medical practitioners, and activists, examines the impact of urban living on the well-being of women and girls in Africa, Asia, Latin America, and the United States.